O vôo dos pássaros: uma reflexão sobre o lugar do contador de histórias na contemporaneidade - Catenacci, Vivian Silva (2008)
Modernity identified the practice of telling stories against a background of tradition, involving people who were illiterate, peasant workers and for this reason fated to disappear. Contrary to popular belief there is now a substantial and continuous growth of this activity in the big cities. This study makes this assumption in order to understand what is specific to the practice in contemporary narrative. This study articulates concepts developed by researchers dedicated to the theme of narration and the world of short stories, by the narrative of storytellers invited to participate in the "II International Meeting of Storytellers" and the video documentary, "Histórias . It is also composed by statements from new storytellers and traditional narrators recorded in researches related to the theme. The story described in this dissertation is based on the experiences of the researcher, as listener and narrator, in raising and drawing up the issues investigated. This paper is divided into three chapters: the first is dedicated to the specific aspects of the art of oral narrative and the place the storyteller has been relegated to in Modern Times. Chapter two considers the changes which have occurred in the narrative practices under the influences of a society in transition. The last chapter presents a reflection on the skills of the storyteller in the contemporary context